The Digital Vortex: Exploring Contemporary New Addictions Among Young People in Italy - Addeo, Felice; D'auria, Valentina; Esposito, Vincenzo; Perrone, Rocco (Italian Sociological Review, 2024)
In recent years, the study of behavioural addictions has increased dramatically (Sixto-Costoya et al., 2021) in the number and variety of topics. Behavioral addiction is caused by repetitive behaviours providing short-term pleasure that may turn harmful in the long run and negatively affects other areas of people’s daily life. Among behavioural addictions, we can take into account those related to the digital field, for example, gambling, gaming, shopping, binge-watching, and above all using social networks (Meng et al., 2022). Of all the population groups, young people seem to be the most susceptible to the overuse of digital resources and the most vulnerable at the same time (Wang et al., 2020). For instance, negative early childhood experiences can have lifelong consequences on individuals and make them more vulnerable than others to developing Internet addiction, particularly if they experienced early traumas, emotional or physical abuses, social isolation, and even if parents massively exposed them to the use of the Internet and social media (Dalbudak et al., 2014). Based on previous findings (Addeo et al., 2023) our study intends to explore the main factors (e.g. age cohort, gender, geographical area) lead to develop digital addictions, and deepen the quality of life of younger users in Italy.